2009
DOI: 10.1111/j.1095-8649.2009.02369.x
|View full text |Cite
|
Sign up to set email alerts
|

Population subdivision in Siamese mud carp Henicorhynchus siamensis in the Mekong River basin: implications for management

Abstract: A molecular approach was employed to investigate stock structure in Siamese mud carp Henicorhynchus siamensis populations collected from 14 sites across mainland south-east Asia, with the major focus being the lower Mekong River basin. Spatial analysis of a mitochondrial DNA fragment (ATPase 6 and 8) identified four stocks in the Mekong River basin that were all significantly differentiated from a population in the nearby Khlong River, Thailand. In the Mekong River basin, populations in northern Lao People's D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 84 publications
2
34
0
Order By: Relevance
“…Therefore, the larger otolith Ba variability does not necessarily translate into longer fish migrations but reflects a greater spatial complexity in water elements encountered by the fish. Due to the unique otolith elemental profiles, H. siamensis from the Thai North likely did not share migration routes with individuals from the other regions, corroborating a finding by Adamson et al [23] who identified a genetically distinct population of the species in this region.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Therefore, the larger otolith Ba variability does not necessarily translate into longer fish migrations but reflects a greater spatial complexity in water elements encountered by the fish. Due to the unique otolith elemental profiles, H. siamensis from the Thai North likely did not share migration routes with individuals from the other regions, corroborating a finding by Adamson et al [23] who identified a genetically distinct population of the species in this region.…”
Section: Discussionsupporting
confidence: 85%
“…Elemental profiles largely overlapped between Mun, Tonle Sap and MM with no significant differences in Sr or Ba at both otolith core and surface. However, because the genetic analysis identified a single stock of H. siamensis below the Khone Falls [23], H. siamensis in the Mun River, which connects with MM above the Khone Falls, likely have a different natal origin from fish in Tonle Sap or MM. During the peak flood season, the Mekong River water causes the Tonle Sap River to reverse its flow [50], likely mixing the water and homogenizing elemental signatures throughout the vast geographical extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility is the existence of a physical barrier. The Khone Falls lie at the national border between Lao PDRand Cambodia, and these falls definitely represent a significant barrier to upstream dispersal of a common cyprinid fish (Adamson et al, 2009). However, this physical barrier is most likely not responsible for the genetic differences we observed because other fish species are able to migrate to the upper side of the river across the falls (Baird, Flaherty & Phylavanh, 2003;Mekong River Commission, 2004).…”
Section: Structurementioning
confidence: 99%